Pola Kemitraan antara Taman Ayu Agrowisata dengan Petani Kopi Luwak - LARASTI, NI LUH MADE BINTANG; SUSRUSA, KETUT BUDI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.9, No.2, Juli 2020, 2020)
Partnership Pattern Between Taman Ayu Agrotourism and Luwak Coffee Farmers Taman Ayu Agro Tourism is a company engaged in the production of bali coffee, ginseng coffee, luwak coffee.Due to the large demand for Luwak coffee, Taman Ayu Agro Tourism has developed a partnership with Luwak coffee farmers in Batukaang Village, Kintamani District, Bangli Regency. This study aims to: (1) know the Partnership Patterns between Taman Ayu Agrowisata and Luwak coffee farmers, (2) know the Effectiveness and Benefits of the partnership between Taman Ayu Agro Tourism and Luwak coffee farmers, (3) know whether the Partnership Pattern increasedfarmers income. Research location was Batukaang VillageBatukaang Village. Data collection is carried out from February to April 2019. The results of the study revealed that: (1) the partnership pattern applied by Taman Ayu Agro Tourism with Luwak coffee was a sub contract. (2) Effectiveness of Cooperation between Taman Ayu Agro Tourism has fulfilled the effectiveness criteria taht was above 80%. The benefits was received by both parties for their business. (3) the income of partner coffee farmers was IDR 26.088.605 per year while non-partner farmers IDRwas16.234.000 per year. Income of partner coffee farmers per musang luwak ( paradoxurushermaphroditus ) per year was IDR 3.178.810 and non-partners was IDR 1.863.852.